Exploring the pharmacological potential and bioactive components of Pogostemon cablin (Blanco) Benth, traditional Chinese medicine - Sonia Singh; Nitin Agrawal (Elsevier, 2024)
Introduction: Pogostemon cablin Benth, commonly referred to as Patchouli, is a fragrant herbaceous plant belonging to the Lamiaceae family. The main aim of cultivating this herb is to extract its oil, which is widely utilised in the manufacturing of cosmetics, fragrances, beverages, foods, and pharmaceuticals. Materials and methods: The data was gathered from electronic repositories that included Science Direct, Web of Science, Scopus, and PubMed. The study selection criteria encompassed the examination of research publications that focused on phytochemical elements, namely bioactive chemicals. Additionally, the pharmacological profile of the herb, as well as relevant book chapters containing botanical, geographical descriptions and morphology, were taken into consideration. Results: Patchouli alcohol (PA) is a primary component found in the oil. PA, which is present in higher proportions in the patchouli plant, is employed as a quality indicator. Norpatchoulene, a chemical compound containing PA, is an extra component that contributes to the distinctive resemblance of the fragrance to patchouli oil. Oil is predominantly recognised for its aromatic properties, characterised by a warm, spicy, and alluring scent. Java accounts for more than 66 % of the worldwide oil output, with China and Malaysia occupying the second and third positions, respectively. In Chinese medicine, the utilization of this herb is employed for the treatment of many ailments, such as headaches, nausea, colds, and diarrhoea. Oil has been utilized as a hair conditioner and in aromatherapy. Guanghuoxiang or patchouli is one of the primary ingredients utilised in the composition of some renowned Chinese patent medications, such as Huoxiang Zhengqi Koufuye (oral liquid) and Baoji Pian (tablets). Discussion: The utilisation of patchouli plants in traditional medicinal systems has been extensive in China and India, where they have been employed for the treatment of many medical conditions. The main objective of this paper is to facilitate the broad appeal of comprehensive research findings related to the pharmacology and pharmacognosy of herbs, by relying upon the existing reservoir of literature in the field.